2013
DOI: 10.1590/s0001-37652013005000009
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 activation and increased procollagen type I in irradiated hearts

Abstract: The caspase-3-cleaved presence was evaluated in this study in the heart of irradiated rats, during the decline of ventricular function. Female Wistar rats were irradiated with a single dose of radiation (15 Gy) delivered directly to the heart and the molecular, histological and physiological evaluations were performed at thirteen months post-irradiation. The expressions of procollagen type I, TGF-ß1 and caspase-3-cleaved were analyzed using Western blotting. Cardiac structural and functional alterations were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…These results are in accordance with radiation-induced apoptosis in other organs, showing increased numbers of apoptotic cells from 6 h to several weeks after irradiation (3638). However, a recent study has demonstrated the presence of cleaved–caspase 3 at 13 months after local heart irradiation in the rat (14). Hence, we cannot exclude that apoptosis may occur again at time points beyond 9 months in our rat model of local heart irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in accordance with radiation-induced apoptosis in other organs, showing increased numbers of apoptotic cells from 6 h to several weeks after irradiation (3638). However, a recent study has demonstrated the presence of cleaved–caspase 3 at 13 months after local heart irradiation in the rat (14). Hence, we cannot exclude that apoptosis may occur again at time points beyond 9 months in our rat model of local heart irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mitochondria are sensitive to radiation and become a direct target of radiation damage within hours after exposure (12). Studies have shown that local heart irradiation can cause morphological damage in cardiac mitochondria (13, 14), and nontransient mitochondrial functional alterations including impairment of the respiratory chain and increased protein oxidation (15, 16). Irradiation has also been shown to increase the mitochondrial mass of certain cells in culture (1719).…”
Section: Introductionmentioning
confidence: 99%
“…Those are characteristcs of healthy cardiac tissue, as shown in the literature by echocardiography, electron microscopy, diffusion tensor (DT) and Magnetic Resonance (MR) images acquired ex vivo [54] [55]. Cardiotoxic agents causes alterations in this pattern, including disorganization of myofibrils and mitochondria, vacuolization of the cytoplasm, and degeneration of crista inside the mitochondria [56] that we could observe on the Figure 2 We can note that previous studies cited in this work did not use any image technique to obtain low-Z elemental and structural information about the health tissue although, it is important to know how some elements are distributed to study any problem on the cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although a large number of centers still uses 2 D tangential breast radiation fields, the present doses to the coronary may be considerably less when modern techniques such as IMRT and VMAT are used in association with CT images for better target delineation. In order to study the possible involvement of fibrosis and apoptosis in this process, the presence of proc-I, TGF-b1, and caspase-3-cleaved were evaluated (Ferreira-Machado et al 2013). Female Wistar rats were given a single radiation dose of 15 Gy.…”
Section: Cardiotoxicity Induced By Radiotherapymentioning
confidence: 99%